MODEL PENGEMBANGAN BUMDES DI WILAYAH KECAMATAN TAJUR HALANG BOGOR - Santosa, Agus; Kuncoro, Setyo; Priyanto, Agus (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This research analyzes the factors that become obstacles in the development of BUMDes in Tajur Halang Sub-district, Bogor Regency, because there are still many villages that have not developed BUMDes in their villages, including villages in Tajur Halang Sub-district. The purpose of this research is to improve the economy of village communities through the development of BUMDes. The method used is qualitative data analysis with three main stages, namely data reduction, data presentation, and conclusion drawing with a pentahelix model approach. The results showed that BUMDes in Tajur Halang Sub-district are generally still under development. BUMDes in Tajur Halang Sub-district require collaboration between universities, business actors, community, and government. Partnerships with various local parties, including MSMEs, are a vital strategy in developing various business sectors. Support from village, sub-district and district governments is also important, although sometimes constrained by local politics. Mass and social media can be used to raise public awareness of BUMDes products and services. However, the success of BUMDes also depends on the spirit and integrity of the BUMDes management in realizing the vision and mission for mutual progress